2016
DOI: 10.1177/0895904815586855
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Self-Efficacy, Professional Commitment, and High-Stakes Teacher Evaluation Policy in Louisiana

Abstract: Currently, a significant number of states are in the process of implementing a high-stakes teacher evaluation (HSTE) system. In many ways, Louisiana’s teacher evaluation system, Compass, is typical of the models that many states have adopted. This article reports the experiences of 37 elementary teachers from five districts across Louisiana after their first 2 years under this system. It is through the multiple lenses of teacher support, autonomy, self-efficacy, and satisfaction that we sought to understand ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 87 publications
(135 reference statements)
2
64
0
3
Order By: Relevance
“…Though the evidence on performance or "merit" based pay is mixed, several recent experimental evaluation studies revealed limited, if any, change in student achievement, teacher motivation, attitudes, or instructional practice over time (Marsh et al, 2011;Springer et al, 2012;Yuan et al, 2013). Furthermore, recent scholarship has revealed some unintended consequences of current U.S. teacher evaluation policy, such as: lack of support and/or guidance in the use of teacher evaluation results (Amrein-Beardsley & Collins, 2012;Ford et al, 2017); lack of validity and/or reliability (either real or perceived) of evaluation results (Darling-Hammond et al, 2012;Ford et al, 2016;Jiang, Sporte, & Luppescu, 2015;Longo-Schmid, 2016;Reddy et al, 2017); and evidence of increase in adverse affective states for teachers subjected to high-stakes evaluation, such as high stress and anxiety as well as decreased job satisfaction, professional commitment, and turnover (Ford et al, 2017;Hewitt, 2015;Holloway & Brass, 2017;Ingersoll et al, 2016;Jiang et al, 2015).…”
Section: The Landscape Of "New" Teacher Evaluation In the United Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…Though the evidence on performance or "merit" based pay is mixed, several recent experimental evaluation studies revealed limited, if any, change in student achievement, teacher motivation, attitudes, or instructional practice over time (Marsh et al, 2011;Springer et al, 2012;Yuan et al, 2013). Furthermore, recent scholarship has revealed some unintended consequences of current U.S. teacher evaluation policy, such as: lack of support and/or guidance in the use of teacher evaluation results (Amrein-Beardsley & Collins, 2012;Ford et al, 2017); lack of validity and/or reliability (either real or perceived) of evaluation results (Darling-Hammond et al, 2012;Ford et al, 2016;Jiang, Sporte, & Luppescu, 2015;Longo-Schmid, 2016;Reddy et al, 2017); and evidence of increase in adverse affective states for teachers subjected to high-stakes evaluation, such as high stress and anxiety as well as decreased job satisfaction, professional commitment, and turnover (Ford et al, 2017;Hewitt, 2015;Holloway & Brass, 2017;Ingersoll et al, 2016;Jiang et al, 2015).…”
Section: The Landscape Of "New" Teacher Evaluation In the United Statesmentioning
confidence: 99%
“…When considered together, these trends in current education policy mark an important shift in the nature and scope of teacher professionalism, and this has implications for how teachers view their work and the satisfaction they derive from it (Ford et al, 2017;Hargreaves, 2010;Holloway & Brass, 2017;Torres & Weiner, 2018). In her work in the sociology of professions, Evetts (2009Evetts ( , 2011 distinguishes between occupational and organizational professionalism, with the former denoting a professionalism characterized by partnership, collegiality, autonomy, and trust, and the latter a professionalism of bureaucratic and hierarchical control, standardization, and hyperrationality.…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, al tratarse de herramientas con fuerte conexión en la teoría, con estándares altamente exigentes, corren el riesgo de perder utilidad, mostrando poca capacidad de discriminación entre una buena y una mala sala de clases (CALLAHAN; SADEGHI, 2015), poniendo alta presión sobre los docentes y las escuelas al asociar algún tipo de consecuencias a la evaluación con estos instrumentos. En otras palabras, los instrumentos corren el riesgo de tomar distancia de los escenarios empíricos, perdiendo utilidad para el mejoramiento de las prácticas y el desarrollo profesional (CALLAHAN;SADEGHI, 2015;SANTIAGO et al, 2013;FORD et al, 2015), y generando un efecto nocivo en las salas de clase por su uso para el accountability (FORD et al, 2015). Es preciso, por lo tanto, volver a mirar estos instrumentos de observación de aula y los rasgos de enseñanza efectiva que los sustentan, y contrastarlos con lo que realmente ocurre al interior de las aulas.…”
Section: Introductionunclassified